Analysis of the influence of clearance on bending stiffness of space deployable mechanism in the locked state. Issue 1 (1st January 2023) - Wang, Xinyuan; Shui, Yongtao; Wang, Chaozheng; Yin, Dezheng; Ji, Hongjuan
Abstract: The future space station, which can simulate the gravity environment by rotation, has attracted the attention of scholars in recent years. It is considered a feasible scheme to fold the mechanism on the ground and assemble it into an artificial gravity ring after entering orbit. The deployable mechanism used to attach the space station is required to be large-scale and sufficiently high stiffness after deployment to ensure the safety and accuracy of the payload. However, the clearance will significantly reduce the stiffness of the mechanism, which is in the locked state. In this paper, the deployable mechanism with enhanced bending and torsion resistance configuration will be taken as the research object. First, based on the classical hinge stiffness model, the hinge equivalent model and the sliding joint equivalent model are proposed. Then, the finite element model based on equivalent stiffness is analyzed, and the effectiveness of the finite element model is verified by comparing the experimental results. Finally, the finite element model was used to analyze the influence of the clearance of the pin hole, the clearance of the sliding fit, and the position of the clearance on the bending stiffness of the deployable mechanism. The results show that the clearance greatly reduces the stiffness of the mechanism under small loads and weakens the bearing performance of components. At the same time, the position of the clearance should be taken seriously in the mechanism design.